2013
DOI: 10.3762/bjoc.9.126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the tetracyclic core of Illicium sesquiterpenes using an organocatalyzed asymmetric Robinson annulation

Abstract: SummaryAn enantioselective synthesis of the core framework of neurotrophic Illicium majucin-type sesquiterpenes is described here. This strategy is based on an organocatalyzed asymmetric Robinson annulation and provides an efficient approach for a diversity-oriented synthesis of Illicium natural products that holds remarkable therapeutic potential for neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 115 publications
1
5
0
1
Order By: Relevance
“…In the HMBC spectrum, the long-range correlations of H-13/C-9 and C-2, H-2/C-9 and C-4, H-3/C-4 and C-9, revealed the presence of a five-membered ring (A ring) ( Figure 2). The other HMBC correlations and the 13 C NMR chemical shift values were similar to those of jiadifenone (4), which has the same B and C rings as majucin-type sesquiterpenoids without the δ-lactone ring. The relative configuration of compound 3 was defined by a NOESY experiment ( Figure 4) in which correlations between H-1 and H-7, H-7 and H-11 were exhibited, indicating that compound 3 possessed the same relative configuration as those of jiadifenone (4).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In the HMBC spectrum, the long-range correlations of H-13/C-9 and C-2, H-2/C-9 and C-4, H-3/C-4 and C-9, revealed the presence of a five-membered ring (A ring) ( Figure 2). The other HMBC correlations and the 13 C NMR chemical shift values were similar to those of jiadifenone (4), which has the same B and C rings as majucin-type sesquiterpenoids without the δ-lactone ring. The relative configuration of compound 3 was defined by a NOESY experiment ( Figure 4) in which correlations between H-1 and H-7, H-7 and H-11 were exhibited, indicating that compound 3 possessed the same relative configuration as those of jiadifenone (4).…”
Section: Resultssupporting
confidence: 53%
“…[3] This family of neurotrophic sesquiterpenes has been the focus of extensive synthetic studies. [4] Many compounds from natural sources and related molecules, such as sesquiterpenoids, [5,6] diterpenoids, [7] steroids and alkaloids exhibit potentiating activities of NGF-induced neurite outgrowth in PC12 cells. [8,9] To further research for agents that promote regeneration and growth of neurons, we further investigated the chemical constituents of the fruits of I. jiadifengpi collected in the south China, resulting in the first isolation of two seco-prezizaane-type sesquiterpenoids named jiadifenlactone acid monomethyl ester (1) and jiadifenin (3), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2016, our group at the Forensic Science Center (FSC) at the Lawrence Livermore National Laboratory (LLNL) has reported the use of the salt TMO in the derivatization of phosphonic acids related to OPNAs [ 85 , 86 , 87 ] ( Figure 4 ). Our interest in this salt originated from our knowledge that alkyloxonium salts, out of which Meerwein’s reagent (triethyloxonium tetrafluoroborate) is the most famous, have found a plethora of applications in the field of total synthesis due to their reactivity and thus their ability to alkylate hindered hydroxyl [ 88 , 89 , 90 ] and carboxylic acid groups [ 91 , 92 , 93 ]. Some key characteristics of the reagent sparked our interest in testing as potential option to DM during analyte methylation reactions for GC-MS analyses.…”
Section: Methylation Methodsmentioning
confidence: 99%
“…Notably, the Danishefsky [87] and Theodorakis research groups [95] have independently performed such studies on the jiadifenin structural motif and have identified several compounds, such as 75 , ODNM ( 16 ), 76 , and 77 , which are more potent than the parent natural products in promoting neurite outgrowth. The neurotrophic effects were evaluated by measuring the stimulation of NGF-mediated neurite outgrowth in PC-12 cells.…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%